2015
DOI: 10.1002/mc.22386
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity oftrans-chalcone in osteosarcoma: Involvement of Sp1 and p53

Abstract: Osteosarcoma is the most common bone cancer. Although the emergence of multidrug therapies has improved available treatments for osteosarcoma, approximately 30% of patients will still develop metastasis. Currently, much anticancer therapy uses drugs that affect oncogenes/tumor suppressor genes, such as p53 (up-regulation) and Sp1 (down-regulation). Chalcones are secondary metabolites of plants and have been demonstrated to induce apoptosis in human cancer cells. Building on this knowledge, we evaluated the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…p53 is widely acknowledged to play a key role in apoptosis, including induction of apoptosis, cell-cycle regulation, differentiation, gene amplification, DNA recombination, and cellular senescence. 27 Meanwhile, in vivo, Sp1 silencing seemed to be effective in terms of reducing vascular apoptosis. Therefore, it could serve as an explanation of the protective role of Sp1 silencing or inhibition in regulating vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p53 is widely acknowledged to play a key role in apoptosis, including induction of apoptosis, cell-cycle regulation, differentiation, gene amplification, DNA recombination, and cellular senescence. 27 Meanwhile, in vivo, Sp1 silencing seemed to be effective in terms of reducing vascular apoptosis. Therefore, it could serve as an explanation of the protective role of Sp1 silencing or inhibition in regulating vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…In the current experiments, the silencing or inhibition of Sp1 strongly downregulated apoptosis and MVs release, which furthermore protected the aorta from calcification. p53 is widely acknowledged to play a key role in apoptosis, including induction of apoptosis, cell‐cycle regulation, differentiation, gene amplification, DNA recombination, and cellular senescence . Meanwhile, in vivo, Sp1 silencing seemed to be effective in terms of reducing vascular apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we found that 1 inhibits TOPOIIa mRNA transcription. This inhibition is probably related to the modulation of p53 and Sp1 by 1, which reduces Sp1 protein expression and increases p53 expression [14,22].…”
Section: Aminochalcone 11 Inhibits Mrna Expression Of Topoiia and Tp5mentioning
confidence: 99%
“…Considering the important roles of p53, Sp1 and topoisomerase IIa in cell cycle progression and apoptosis [21,22,27] and the higher cytotoxic and pro-apoptotic effects of the aminochalcones compared to 1 in DH82 cells (Table 1), we used quantitative RT-PCR to investigate mRNA expression of the corresponding TP53, Sp1 and TOPOIIa genes in DH82 and MDCK cells treated with aminochalcones 3, 4 and 11 for 24 h (Fig. 3).…”
Section: Aminochalcone 11 Inhibits Mrna Expression Of Topoiia and Tp5mentioning
confidence: 99%
“…1,2 As one of the most important tumor suppressors, p53 is found to be associated with risk of many diseases, including OS. [3][4][5] As a transcription factor, p53 mainly functions through the target gene specific DNA sequence, and transcription regulation of the p53 target gene plays important role in tumor inhibition. 6 Therefore, the genetic variation which located on the binding site of the p53 target gene is likely to influence the transcription of the corresponding target gene by altering the binding power of p53.…”
Section: Introductionmentioning
confidence: 99%